2021
DOI: 10.1007/s10311-021-01279-8
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of adsorption isotherms by statistical physics models: a review

Abstract: Adsorption is a major basic and applied phenomenon in many scientific disciplines. In particular, the design of adsorbents to remove pollutants from wastewater requires advanced knowledge of adsorption isotherms, which are useful tools to identify physicochemical factors that control adsorption performance. Recent modeling of adsorption isotherms has focused on the use of statistical physics. Here, we review the major adsorption isotherm models based on statistical physics. We discuss steric, energetic, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 98 publications
3
52
0
Order By: Relevance
“…Calculated steric parameters nAs and DLaX for the arsenic adsorption on N-La10 and C-La10 are reported in Table 3. Results showed that the arsenic adsorption on the surfaces of both adsorbents was a multi-molecular process (i.e., nAs > 1) especially at 25 °C where more than one arsenic anion could interact with a lanthanum functionality via an inclined or perpendicular adsorption position (Amrhar et al, 2021). However, the adsorption orientation of arsenic anions on adsorbent surfaces changed as the solution temperature increased where a potential multi-anchorage of this geogenic pollutant could occur at > 30 °C.…”
Section: Comparison Of Activation Strategies Of Lanthanum-functionali...mentioning
confidence: 97%
See 1 more Smart Citation
“…Calculated steric parameters nAs and DLaX for the arsenic adsorption on N-La10 and C-La10 are reported in Table 3. Results showed that the arsenic adsorption on the surfaces of both adsorbents was a multi-molecular process (i.e., nAs > 1) especially at 25 °C where more than one arsenic anion could interact with a lanthanum functionality via an inclined or perpendicular adsorption position (Amrhar et al, 2021). However, the adsorption orientation of arsenic anions on adsorbent surfaces changed as the solution temperature increased where a potential multi-anchorage of this geogenic pollutant could occur at > 30 °C.…”
Section: Comparison Of Activation Strategies Of Lanthanum-functionali...mentioning
confidence: 97%
“…It is convenient to remark that lanthanum has a great affinity for anions, makes stable compounds with them and has the possibility of interacting simultaneously with several arsenic anions due to its valence (Wang et al, 2016;Lingamdinne et al, 2019). Therefore, this adsorption model is given by (Amrhar et al, 2021)…”
Section: Arsenic Adsorption Using the Engineered Lanthanum-functional...mentioning
confidence: 99%
“…These molecules exist in various forms, such as alkali metals, alkaline earth metals, transition metals, and non-metals (Dahou et al 2021). While such elements only account for negligible proportion, they could be dissolved in the polluted solutions and thus lower the biosorption capacity of raw biomass (Amrhar et al 2021). Regardless of the little concern or even lack in the material preparation method, the explants could be generally washed by distilled water at ambient temperature before drying (Bansal et al 2021).…”
Section: Cleaning the Biomassmentioning
confidence: 99%
“…This model assumed that several molecules of adsorbate (i.e., IA) can form multilayers (i.e., clusters) onto the adsorbent surface (i.e., CSK6). Details and fundaments of this model can be found in the review of Amrhar et al [31]. Therefore, the adsorption capacity can be defined by this model with the next equations [31].…”
Section: Adsorption Mechanism In the Ia Separation With Thementioning
confidence: 99%